Smallpox outbreaks and immunization policies in Tanzania from the late nineteenth century to the First World War. - Larson, Lorne (Zamani: A Journal of African Historical Studies, 2024)
An estimated 300 million people died globally from smallpox in the 20th century alone. There was very much a North/South divide in the existence of the disease in that period, with countries across South America, Africa and Asia recording the majority of cases. In 1966 the World Health Organization launched an intensive effort to finally eliminate the disease. The last known endemic case of smallpox was reported in Somalia in 1977, and that outbreak was promptly contained. In 1980 smallpox was declared eradicated – the only infectious disease affecting humans to achieve this distinction. This remains among the most notable and profound public health successes in history. This essay steps back to the first two decades of the twentieth century and considers the smallpox context that evolved in the political entity of German East Africa but alters it slightly to correspond more closely to the modern state of Tanzania, in short, paying minor attention to the residencies of Ruanda and Urundi and rather more attention to the Zanzibari islands in the Indian Ocean.